Valorization of Cork Residues for Biomass Pellet Production: Meeting ENplus® Standards Through Strategic Blending - Amadeu D. S. Borges; Paulo Matos; Miguel Oliveira (Clean Technologies, 2025)
Cork processing generates significant by-products that pose environmental challenges and waste management concerns. This study investigates the potential of utilizing cork residues—finishing powders, grinding powders, and sawdust—for biomass pellet production, emphasizing compliance with ENplus® A1, A2, and B standards. Physical, chemical, and calorimetric analyses reveal that sawdust is the only material capable of independently meeting ENplus® requirements, due to its low nitrogen (0.19%) and ash (0.22%) contents. However, its low net heating value necessitates blending with cork residues for improved energy performance. Finishing powders, despite a high net heating value (17.36 MJ/kg) and low ash content (0.37%), are restricted by their elevated nitrogen levels (1.59%). Grinding powders, with net heating values ranging from 16.25 to 17.78 MJ/kg, offer limited suitability due to high ash and nitrogen contents. For Class A1, mixtures require 85–87% sawdust, limiting cork residue incorporation to 15%. For Class A2, sawdust inclusion drops to 65–70%, allowing for greater use of cork residues and boosting net heating values to 16.74 MJ/kg. Class B mixtures achieve the highest incorporation of cork residues (up to 65%), with net heating values reaching 16.92 MJ/kg, suitable for industrial applications. These results highlight blending strategies as essential for balancing regulatory compliance, energy efficiency, and waste valorization. Future research should focus on pretreatment methods, alternative biomass sources, and lifecycle assessments to enhance compliance and scalability, promoting sustainable energy solutions and circular economy goals.